Sex determination in Drosophila: the X-chromosomal gene liz is required for Sxl activity. - Steinmann-Zwicky, M (1988)
In Drosophila, females require products of the gene Sxl for sex determination, dosage compensation and fertility. I show here that the X-chromosomal gene liz, located in 4F1 to 4F11 and previously called fs(1)1621, provides maternal and zygotic functions necessary for Sxl activity in germ line and soma. In XX animals, the mutation SxlM1 which was reported to express the female-specific functions of Sxl constitutively can rescue all phenotypes resulting from lack of liz product. XY animals carrying SxlM1 and lacking maternal or zygotic liz activity survive as males with some female traits. A stock was constructed in which the females are liz SxlM1/liz SxlM1 and males liz SxlM1/Y. This shows that SxlM1 is not truly expressed constitutively in animals with an X:A ratio of 0.5, but requires activity of liz for initiation or maintenance.